1986
DOI: 10.1002/hep.1840060121
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin in Bleeding Esophageal Varices: A Placebo–Controlled, Double–Blind Study

Abstract: The effect of terlipressin (N-alpha-triglycyl-8-lysine-vasopressin) in bleeding esophageal varices was evaluated in a prospective placebo-controlled study. Fifty bleeding episodes from esophageal varices in 34 patients were randomized. Standard therapy with transfusions, fluid and electrolyte correction, and lactulose was performed in both groups. Balloon tamponade was used in 20 bleeding episodes in the terlipressin group and in 19 bleeding episodes in the control group. In the terlipressin group, hemorrhage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(39 citation statements)
references
References 19 publications
0
36
0
3
Order By: Relevance
“…5 This has encouraged the search for pharmacologic alternatives overcoming these limitations. Recent large randomized controlled trials (RCTs) showed that terlipressin effectively controls variceal bleeding with a low rate of side-effects [6][7][8][9][10][11][12] even when used for an extended period. 13,14 Terlipressin has optimal applicability, does not require specialized staff or sophisticated equipment, and is the only drug shown to improve survival from variceal bleeding in placebocontrolled trials 9,15 and meta-analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 This has encouraged the search for pharmacologic alternatives overcoming these limitations. Recent large randomized controlled trials (RCTs) showed that terlipressin effectively controls variceal bleeding with a low rate of side-effects [6][7][8][9][10][11][12] even when used for an extended period. 13,14 Terlipressin has optimal applicability, does not require specialized staff or sophisticated equipment, and is the only drug shown to improve survival from variceal bleeding in placebocontrolled trials 9,15 and meta-analyses.…”
mentioning
confidence: 99%
“…The sample size calculation was based on the results of 10 published studies for terlipressin and 15 for emergency sclerotherapy (at the time the study was planned). The estimated overall failure rate for terlipressin was 40% (failure to control bleeding 20% ϩ development of early rebleeding 20%), [6][7][8][9][10][11][12][13]15,16 and 30% (10% ϩ 20%, respectively) for sclerotherapy. 3,14,[17][18][19] The sample size needed to detect clinical equivalence (a difference lower than the maximum expected, was established at 10%) in efficacy was calculated as 83 patients on each arm using a 2-sided test with 80% power at a significance level of 5%.…”
mentioning
confidence: 99%
“…14 Placebo-controlled trials have shown that TP is effective in controlling variceal bleeding and, more importantly, in reducing the mortality from variceal hemorrhage. [15][16][17][18] Additional randomized, controlled studies have further shown that TP is more effective and safer than VP (alone or combined with nitroglycerin), 19,20 and may prevent early rebleeding when administered for prolonged periods. 21 To date, TP is the only agent to have a significant effect on mortality from variceal hemorrhage.…”
mentioning
confidence: 99%
“…After this time, if the bleeding is controlled, the dosage should be reduced by half. Five days of dosing should not be exceeded (31,32,33).…”
Section: Vasoactive Drugsmentioning
confidence: 99%